Fine Structure of Whistler Mode Hiss in Plasmaspheric Plumes Observed by the Van Allen Probes. Issue 11 (8th November 2018) - Nakamura, S.; Omura, Y.; Summers, D.
Abstract: We survey 3 years (2013–2015) of data from the Van Allen Probes related to plasmaspheric plume crossing events. We detect 194 plume crossing events, and we find that 97% of the plumes are accompanied by very low frequency hiss emissions. The plumes are mainly detected on the duskside or dayside. Careful examination of the hiss spectra reveals that all hiss emissions consist of obvious fine structure. Application of a band‐pass filter reveals that the fine structure is consistent with the occurrence of discrete wave packets. The hiss data display high coherency. The events are classified by location. Duskside hiss and nightside hiss tend to have extremely high polarization with no chorus at the high‐frequency end of the dynamic spectrum. The duskside hiss has a distinct upper frequency limit. On the other hand, the dawnside hiss has strong chorus elements at the upper hiss frequency, which makes the upper frequency limit ambiguous. We show that the structure of whistler mode hiss is different from artificial random noise. Although noise also has fine spectral characteristics, the polarization and waveform data are totally different from the hiss cases. Our results strongly suggest that whistler mode hiss in plasmaspheric plumes universally possesses fine structure. Key Points: We examine 194 plume crossing events observed by the Van Allen Probes We observe hiss emissions in 97% of the plume events All hiss emissions have obvious fine structure